Lactose loading test on protein calorie malnutrition - Sunoto Sunoto; Suharjono Suharjono; Cysca M. Lembong; Aswitha Budiarso; Samsudin Samsudin (Paediatrica Indonesiana, 1973)
Diarrhoea is a common feature of severe cases of malnutrition andusually pathogenic agents can not be isolated. Abnormal intestinal motility is not a primary feature of the diarrhoea iu malnourished children(James, 1968). Sugar intolerance is considered Ii common cause of diarrhoea in children with kwashiorkor admitted to hospital in Kampala(Wharton et ai., 1968). Dean (1957) originally suggested that the lactoseof milk was the cause of severe diarrhoea encountered in cases of advanced kwashiorkor.